Detecting smart contract vulnerability - Chen, QiuRong (Nanyang Technological University, 2023)
Smart contracts have become fundamental to decentralised applications with the increasing adoption of blockchain technology. Often, due to its immutable nature combined with the high-value transactions it carries, it has become the prime target for malicious threat actors. A simple arithmetic error or bug in the code can lead to significant financial losses to individuals or institutions. By leveraging a combination of static and dynamic code analysis, this project provides developers with a tool to identify and rectify potential threats before deploying to the main net of the blockchain.